Learning programming using educational robotics - Aparicio, Joao Tiago (2019)
Aparicio, J. T., Pereira, S., Aparicio, M., & Costa, C. J. (2019). Learning programming using educational robotics. In R. Goncalves, I. Pedrosa, M. P. Cota, & A. Rocha (Eds.), 2019 14th Iberian Conference on Information Systems and Technologies (CISTI) [8760709] (Iberian Conference on Information Systems and Technologies, CISTI; Vol. 2019-June). IEEE Computer Society. https://doi.org/10.23919/CISTI.2019.8760709